Using social media listening to identify the real-world challenges faced by dog owners globally when administering oral medications - Tarrant, Georgina; Rai, Taranpreet; Wright, Andrea; Street, Travis; Wells, Kevin (Frontiers in Veterinary Science, 2025)
IntroductionPet owner compliance with oral medication administration represents a significant challenge in veterinary medicine, yet limited real-world data exists on the experiences and barriers faced by dog owners during at-home “pilling” processes.MethodsThis study employed social media listening (SML) to analyze 4,787 relevant posts from X, Reddit, Facebook, blogs, and forums discussing oral medication administration to dogs. Large language models (LLMs) were used for data cleaning, relevancy filtering and analysis. Topic modeling, sentiment and thematic analyses were conducted to identify key themes and challenges.ResultsAnalysis revealed significant anxiety and fear associated with medication administration, with 12% of posts mentioning anxiety and additional fear-related terms appearing in 1-3% of posts. Only 7.6% of posts discussed soft/chewable medications, which showed positive sentiment and preference. Geographic analysis showed posts predominantly from English-speaking countries (US 70.3%, UK 17.8%). Five major themes emerged from X, Reddit, blogs and forums: general medication/veterinary experiences, pill types and practices, pill delivery methods, specific medications/preventatives, product reviews/natural remedies. Financial concerns were prominent, with pet owners describing medication costs as barriers to optimal care. Successful pilling strategies included hiding pills in peanut butter, cheese or meat products; crushing pills and mixing with food, and using distraction techniques.DiscussionThe study identified key barriers to compliance including financial constraints, fear and anxiety, mistrust of veterinary advice and practical administration challenges. Pet owners showed higher adherence when treatments visibly improved quality of life or addressed chronic conditions. Chewable formulations were preferred but raised concerns about accidental overdosing. The methodology demonstrated that SML combined with AI analysis effectively captures real-world pet owner experiences.ConclusionsThis novel approach revealed that dog owners face significant psychological and practical barriers when administering oral medications. Chewable formulations may improve compliance, though proper storage and education are essential. The study provides veterinarians with evidence-based successful pilling strategies reported by pet owners and highlights the need for better communication about treatment benefits, financial planning options and alternative delivery methods to improve medication adherence.